(untitled) (Altre Modernità, 2020)
The article traces the observation that waste as an object of research is at the same time an effect of its research. It examines three studies on waste: "Rubbish!" by William Rathje and Cullen Murphy, Guido Viale’s "Un mondo usa e getta", and "Das Müll-System" by Volker Grassmuck and Christian Unverzagt. These studies exemplify three types of presenting waste: ‘exploration’, ‘problem’, and ‘recycling’. Considering them as scientific arguments allows us to discuss what is considered to be ‘waste’ by asking questions of representability and at the same time questioning the consequences representation has for the concept of waste.